Development of the Mata Penida Source in the Drinking Water Supply System on the Island of Nusa Penida - Arsana, I Gusti Ngurah Kerta; Astiti, Sagung Putri Chandra; Dharma, Anak Agung Gede Ngurah Kurnia Teja (Universitas Ibn Khaldun Bogor, 2025)
The need for inadequate water can have a negative impact on health and social conditions. This is also accompanied by an increase in problems related to the quality, quantity and continuity of raw water that can be used as clean water. One area that requires special attention in terms of providing raw water is Nusa Penida Island. The method used in research is quantitative. For the basis of taking drinking water needs based on the increase in existing drinking water needs and hydraulic analysis using the Epanet application. For this reason, optimization needs to be carried out to meet the demand for raw water which continues to increase along with the increasing population in Nusa Penida District. Optimizing water supply can be done by increasing the production capacity of the Penida spring water source by considering a more strategic location. Network optimization design is carried out using manual calculations and the help of the Epanet application to run simulations. Based on the analysis results, in 2038 water demand in Nusa Penida District will reach 138.15 liters/second. Production capacity is currently still experiencing a deficit of 22.52 liters/second so optimization is needed in the Drinking Water Supply System network. The addition of a pump with a capacity of 25 liters/second to the Penida spring, supported by adjustments to pipe dimensions and accessories, could be a solution to overcome the existing deficit. Rejuvenation and realignment of distribution pipes to service areas must also be carried out so that water is distributed evenly throughout the village.